TOBACCO-ALCOHOL TOXIC-NUTRITIONAL OPTIC NEUROPATHY: A CASE REPORT - Pinto, Anderson Gustavo Teixeira; Barroso, Letícia Fernandes; Castro, Bruna Cordeiro Benvenutti; Boni, Carla Duhau; Netto, Gabriela Furlan Ribeiro Barbosa; Gutierres, Gabriela Ponte; Manfroi, Giulia Longoni; Reis, Sara Oliveira (Seven Editora, 2026)
Introduction: Tobacco-alcohol optic neuropathy is a toxic-nutritional condition that causes damage to the optic nerve. While tobacco exerts a predominantly toxic effect, alcohol acts through nutritional deficiency, impairing the bioavailability of essential nutrients such as folate and B-complex vitamins. The pathophysiology is associated with mitochondrial DNA damage and the accumulation of free radicals.Case Report: A 67-year-old male patient, with a history of alcoholism and smoking for more than 30 years, presented with progressive visual loss in the right eye (RE) for two weeks. The left eye (LE) had previous amaurosis due to trauma. On examination, visual acuity in the RE was counting fingers at 1 meter. Complementary examinations revealed temporal pallor of the optic disc and a cecocentral scotoma on computerized visual field testing. Following the diagnosis of tobacco-alcohol optic neuropathy, treatment was initiated with 5000 mcg of intramuscular vitamin B12 weekly for three weeks, in addition to counseling for smoking and alcohol cessation.Results and Conclusion: After treatment, there was significant recovery of the visual field and improvement of visual acuity in the RE to 20/40. The visual prognosis of this condition depends directly on early diagnosis, duration of exposure to toxic substances, and the immediate cessation of alcohol and tobacco use in order to prevent irreversible damage.